Pengaruh Apersepsi Pada Pelajaran Fikih dalam Membangun Kelas Humanis Religius Siswa - Muhammad Arif Faldi Jauhary; Eni Rosidah (Universitas Muhammadiyah Jember, 2019)
Apperception constitutes the initial stage of learning process, but is often missed in the implementation of learning activities. Apperception can help students understand instructional materials. The relation of the learning process to fiqh material is often seen as monotonous and rigid. When fiqh is taught as something doctrinaire, the output will also be droctilary. By contrast, when fiqh is delivered through something that highlights the potential and characteristics of students, these students will be able to relate what they have learned to their real-life activities, leading to humanist and religious classes. The purpose of this study was to determine the relationship between apperception on fiqh instructional materials and the development of humanist classes. This research is a quantitative descriptive study. The population was 40 students. Data were collected through a questionnaire with a random sampling method, and analysed through the product moment correlation. The results showed that apperception in fiqh subjects had an average (19,275) which means it was included in the medium category, building a religious humanist class had an average (18,075) which meant it was included in the medium category. Then the conclusion apperception in fiqh lessons have an influence in building students' religious humanist classes at MTs Miftahul Ulum Kudus.